Mitigating Tax Avoidance: Independent Commissioners, Audit Committees, and CSR in Manufacturing: Mengurangi Penghindaran Pajak: Komisaris Independen, Komite Audit, dan CSR di Perusahaan Manufaktur - Rohmatus Sakdiyah; Wisnu Panggah Setiyono (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative study examines the effect of independent commissioners, audit committees, and Corporate Social Responsibility (CSR) on tax avoidance in the goods and consumption sub-sector of manufacturing companies listed on the Indonesia Stock Exchange from 2016 to 2020. Purposive sampling was employed, resulting in a sample of 21 companies. Secondary data from financial reports were collected and analyzed using descriptive statistics and panel data analysis. The findings reveal that independent commissioners and audit committees do not significantly influence tax avoidance. However, CSR activities have a significant impact on reducing tax avoidance. Furthermore, when considered collectively, independent commissioners, audit committees, and CSR practices exhibit a joint effect on tax avoidance. These findings contribute to the existing literature on corporate governance and taxation, highlighting the role of CSR as a potential tool to mitigate tax avoidance practices in the manufacturing sector. Highlights: The study examines the impact of independent commissioners, audit committees, and CSR on tax avoidance in manufacturing companies. Findings reveal that CSR practices have a significant effect in reducing tax avoidance. The joint influence of independent commissioners, audit committees, and CSR on tax avoidance is also explored. Keywords: tax avoidance, independent commissioners, audit committees, Corporate Social Responsibility (CSR), manufacturing companies